2021
DOI: 10.1590/1980-57642021dn15-040014
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among students with neurodevelopment disorders: case of dyslexic children and adolescents

Abstract: Several research studies have been devoted to study the links between emotional disorders and learning disabilities. However, very minimal of this research has focused on dyslexic students. Objective: The objectives of this study were as follows: (1) to assess self-esteem, anxiety, and depression in dyslexic Arabic-speaking children and adolescents and (2) to describe psychiatric comorbidities in these subjects by comparing them to their non-dyslexic peers. Methods: In total, 205 students (56 dyslexics and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Studies published since this review have mostly supported these findings, with several papers reporting significant associations between anxiety or depression scores and poor reading, sometimes moderated by gender (Anxiety: Aro et al, 2022;Castagna et al, 2021;Elgendi et al, 2021;Ihbour et al, 2021;Macdonald et al, 2021;Tobaoda Barber et al, 2021;Wang, 2021 [girls, but not boys]; and Zuppardo et al, 2021;Depression: Daniel et al, 2006;Ihbour et al, 2021;Maughan et al, 2003 [Grades 1 and 4 boys, but not Grade 7 boys]; and Wang, 2021); and between poor reading and behavioural problems (externalising behaviours).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Studies published since this review have mostly supported these findings, with several papers reporting significant associations between anxiety or depression scores and poor reading, sometimes moderated by gender (Anxiety: Aro et al, 2022;Castagna et al, 2021;Elgendi et al, 2021;Ihbour et al, 2021;Macdonald et al, 2021;Tobaoda Barber et al, 2021;Wang, 2021 [girls, but not boys]; and Zuppardo et al, 2021;Depression: Daniel et al, 2006;Ihbour et al, 2021;Maughan et al, 2003 [Grades 1 and 4 boys, but not Grade 7 boys]; and Wang, 2021); and between poor reading and behavioural problems (externalising behaviours).…”
mentioning
confidence: 56%
“…Though much of this research has focussed on English readers, studies have also examined Italian (Zuppardo et al, 2021), Mandarin (Wang, 2020), Arabic (Ihbour et al, 2021), Finnish (Aro et al, 2022), and Swedish (Kempe et al, 2011) children.…”
mentioning
confidence: 99%
“…The emotional problems examined in our study were assessed by three scales that were already successfully used on the people of Morocco (Ihbour et al, 2021). (1984).…”
Section: Toolsmentioning
confidence: 99%
“…For example, a scoping review conducted by [18] demonstrated that while factors such as self-esteem are often identified in research studies, research focusing on associations between mental health and these factors in the context of dyslexia were limited. Children often talk about worries, stress and embarrassment in the context of their dyslexic symptoms [19], and some links between dyslexia and poorer mental health in terms of higher rates of anxiety, depressive symptoms, and learned helplessness have been found [9,13,15,19]. However, there is a lack of research which investigates how PPIs can have a direct impact on mental health through the improvement of factors such as self-esteem in dyslexic students.…”
Section: Introductionmentioning
confidence: 99%